Diverse polysaccharide production and biofilm formation abilities of clinical Klebsiella pneumoniae - Robert L. Beckman; Elenora Cella; Taj Azarian; Olaya Rendueles; Renee M. Fleeman (npj Biofilms and Microbiomes)
Abstract Klebsiella pneumoniae infections have become a growing threat for human health. The lack of understanding of the relationship between antibiotic resistance, mucoviscosity, and biofilm formation impedes our abilities to effectively predict K. pneumoniae infection outcomes. The Multidrug-Resistant Organism Repository and Surveillance Network offers a unique opportunity into the genetic and phenotypic variabilities in the K. pneumoniae isolates. To this end, we compared the genetic profiles of these isolates with the phenotypic biofilm formation, percent mucoviscosity, and growth rates. There was a significant phenotype-genotype correlation with decreased biofilm formation and an insertion sequence in the transcriptional activator of the type III fimbrial system. Interestingly, the most mucoid strains in the populations were lacking the genetic element regulating the mucoid phenotype and three of these isolates were able to form robust biofilms. The combination of phenotypic, genomic, and image analyses revealed an intricate relation between growth, mucoviscosity and specific virulence-associated genetic determinants.